Vývoj evropských států podle Perryho Andersona - Jan Kalenda (AntropoWebzin)
The text deals with question of European state formation in research of contemporary British sociologist Perry Anderson . Its first intention focus on how modern European medieval and absolutistic states emerged. The article consists from four main parts: (1) Introduction to theory of state-formation. (2) Analysis of structural and analytical connections between state and society in author´s treatise.  (3) Third main part deals with analysis of course of European state-building. On this problem we apply specific analytical model, which distinguish causes, components, progression, and impacts on state formation processes. In this case, author analyzes mechanisms of state building in feudal period 9–15th century and period of absolutistic states (16--19th century). (4) Last part is focuses on conclusion of our findings, especially on drawings specific conceptual model of this process.